Türkiye’ye verilen derecelendirme notlarının doğrudan yabancı yatırım girişine etkisinin yıllar itibariyle incelenmesi - (:unkn) unknown (My University, 2011)
Doğrudan yabancı yatırımlar bir ülkenin ekonomisinin gelişmesinde önemli rol oynarlar. Bundan dolayı devletler yabancı yatırımcıyı ülkelerine çekebilmek istemektedir. Yabancı yatırımcı ülkeye yatırım yapmadan önce ülkenin hukuki, politik ve ekonomik yapısı hakkında bilgiye ihtiyaç duymaktadır. Yatırımcı tarafından ihtiyaç duyulan bu bilgiler uluslararası kredi derecelendirme kuruluşları tarafından verilen kredi derecelendirme notları ile sağlanmaktadır. Bu yüzden ülkelere verilen bu notların doğrudan yabancı yatırım akışı üzerinde ciddi etkisinin olduğuna inanılmaktadır. Uluslararası kredi derecelendirme kuruluşları tarafından Türkiye’ye verilen kredi derecelendirme notlarının doğrudan yabancı yatırım girişine etki edip etmediği bu makalede incelenecektir.

Foreign direct investments play an important role on a country’s economic development. Because of this fact, states want to have flow of foreign investors in their countries. Before investing any capital, foreign investor needs to have information on legal, political and economical structure of the country. The information needed by investors is provided by ratings of international credit rating agencies. Therefore, it has been believed that credit ratings given by credit rating agencies have serious effect on flow of foreign direct investments. The issue of whether credit ratings reported on the credit worthiness of Turkey by international credit rating agencies have any effect on flow of foreign direct investment will be examined in this article.
Examining the effect of the credit ratings reported on creditworthiness of Turkey on flow of foreign direct investment year by year
Keywords: Hukuk